EPIDEMIOLOGY, SOCIO-LEGAL DIMENSIONS, AND POLICY RESPONSES TO CHILD SEXUAL ABUSE IN INDIA - Vidya V V; B Venugopal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Child sexual abuse (CSA) is widespread in India, which poses a critical public health concern of profound epidemiological, socio-legal, and policy relevance. The exorbitantly high rates of prevalence of CSA have been reported to range around 48% for boys and 39% for girls in some of the southern states of India. Yet, the reported incidence could be lower than the actual due to existing societal stigmas, poor awareness, and cultural taboos about sexuality. The findings of this study confirm that risk factors for abuse tend to overlap with socio-economic factors, family relationships, and community organization, highlighting the complex nature of CSA as shaped by patriarchal societal norms and power relations. Combating the epidemic of CSA in India needs to be addressed by an organized effort involving effective legal frameworks, public awareness, community engagement, and ongoing reforms to facilitate successful prevention and rehabilitation. Gap-filling between awareness, removal of socio-cultural stigmas, and introducing effective training programs among the police and judiciary personnel is a crucial step towards eliminating CSA and creating a safe environment for children